Effects of Unilateral Ligamentoplasty on Spinal Development in the Growing Rabbit - Moissonnier, P.; Meunier, A.; Breard, F.; Graf, H. (Veterinary and Comparative Orthopaedics and Traumatology, 1998)
Numerous models of scoliosis have been proposed, but few were characterized geometrically, easily reproductible and avalaible for testing orthopaedic procedures. Sixteen growing rabbits underwent unilateral ligamentoplasty of three lumbar vertebrae using screws in the vertebral body. Spinal modifications were evaluated at six and 12 weeks post-operatively by radiography, scannography and histology. The mean lateral deviation was found to be 21°± 3.1 at six weeks and 41.6 ± 6.6 at 12 weeks. Significant lordosis, cyphosis or vertebral rotation were not observed. Vertebral torsion was significative (p <0.005). Histological assessments of the modifications of paraspinal muscles, intervertebral discs and articular facets were performed for evaluation of consequences of surgery, spinal immobilization and deviation. We concluded that unilateral ligamentoplasty produce a reproductible model of lateral deviation of the spine in the growing rabbit.This article analyses the spinal deformities obtained after unilateral ligamentoplasty of three lumbar vertebrae. A time-dependent lateral deviation and a vertebral torsion were found but significant lordosis, cyphosis or vertebral rotation were not observed. Paraspinal muscles, intervertebral discs and articular facets modifications are reported. Clinical relevance of these data are discussed.
Keywords: Scoliosis; ligamentoplasty; rabbit